PRODUCTIONAL MODEL OF AN ASSESSMENT OF QUALITY OF PROFESSIONAL TRAINING AND EXTENT OF ACHIEVEMENT OF THE OBJECTIVES IN THE FIELD OF QUALITY - Alexander I. Mitin; Tatyana A. Filicheva (Открытое образование (Москва), 2016)
In the article we offer the method which allows to define the extent of the objectives achievement in the field of quality of professional training with application of a fuzzy logical conclusion and hierarchical representation of educational process is offered. Realization of production model of an assessment of extent of achievement of the objectives in the field of quality within information-analytical system of monitoring of quality as subsystem of the general information system of educational institution is described.